ANALYSIS OF THE ADOLESCENT REPRODUCTIVE HEALTH PEER EDUCATOR PROGRAM USING THE DISCREPANCY MODEL AT JUNIOR HIGH SCHOOL IN MOJOKERTO - Catur Prasastia lukita Dewi (International Journal of Nursing and Midwifery Science (IJNMS), 2025)
Reproductive health education is a crucial aspect of youth development. One effective approach to providing reproductive health education is through peer educator programs. To ensure the effectiveness of program implementation, a systematic evaluation model is needed. One such model is the Discrepancy Model, which assesses the extent of the discrepancy between expected conditions (program standards) and actual conditions in the field. The purpose of this study was to analyze the implementation of the adolescent reproductive health peer educator program using the Discrepancy Model at Junior High School in Mojokerto. The approach used was descriptive quantitative, with the aim of describing the extent of the conformity between program standards and their implementation in the field based on the dimensions of the discrepancy model. The sample in this study was all 40 students participating in the Peer Educator program (PIK-R Team) and two mentor teachers. Based on the analysis using the Discrepancy Evaluation Model (DEM), the average conformity score to ideal standards reached 92%, with an average discrepancy of 8%, which is considered good. An average discrepancy below 10% indicates that the gap is still within reasonable limits and can be improved through strengthening training, supervision, and ongoing monitoring.